Fundamentally understanding carbonation-induced corrosion of steel in environmentally friendly concretes - Albert, Cristhiana; Mundra, Shishir; Isgor, O. Burkan; Angst, Ueli (Revista ALCONPAT, 2024)
Reducing greenhouse gas emissions in concrete production is crucial to achieve sustainability goals. One of the primary solutions is employing environmentally friendly cements with lower clinker content, such as those containing supplementary cementitious materials. However, concretes produced with some of these cements are vulnerable to fast carbonation, which raises durability concerns regarding corrosion of the steel reinforcement. While traditional approaches focus on preventing concrete carbonation and corrosion initiation, evidence shows that corrosion rates of steel in carbonated concrete do not necessarily compromise durability. In this context, the fundamental understanding of the kinetics of carbonation-induced corrosion must be improved, considering the role of the concrete pore solution, pore structure, and moisture content, as discussed in this paper. Open questions and promising approaches to clarify them are also discussed. Based on this knowledge, corrosion propagation can be properly included in the service life design of reinforced concrete structures, reconciling the goals for both sustainable and durable structures.